Top soil removal reduces water pollution from phosphorus and dissolved organic matter and lowers methane emissions from rewetted peatlands. Issue 1 (8th June 2017) - Zak, Dominik; Goldhammer, Tobias; Cabezas, Alavaro; Gelbrecht, Jörg; Gurke, Robert; Wagner, Carola; Reuter, Hendrik; Augustin, Jürgen; Klimkowska, Agata; McInnes, Robert
Abstract: A valid strategy to mitigate the eutrophication of water bodies due to non‐point source phosphorus (P) pollution and to reduce the emissions of greenhouse gases is the rewetting of degraded peatlands. However, long‐term drainage and intensive agricultural use make it unlikely that the original sink functions for nutrients and carbon (C) as well as low‐nutrient conditions can be re‐established within a human time perspective. We hypothesized that the removal of the upper degraded peat layer can be a suitable measure to avoid the negative implications of excess mobilization of P and C after rewetting. To evaluate the effect of top soil removal (TSR) we performed lab and field experiments in six inundated peatlands in northern Germany without TSR compared to six inundated sites with TSR. In addition, we included data from a rewetted peatland where the degraded peat had been removed from about half of the area and groundwater level was just beneath the soil surface. The results emphasized that following inundation newly formed detritus mud layers overlying the former peat surface are the dominating source for P and methane in particular in sites without TSR but also in sites with TSR, although at significantly lower rates. Although highly decomposed peat released more or less no methane, dissolved organic matter mobilization was highest in this substrate while less decomposed peat was characterized in general by lowest rates of mobilization. Synthesis and applications . Top soil removal prior to rewetting can be a suitable method to avoid the negative consequences of the excess release of phosphorus (P) and carbon post‐rewetting. We developed a simple decision support schematic to assist the peatland restoration process and to better understand the implications of top soil removal. Despite the potential benefits, top soil removal should not be declared as a universal method, as it requires detailed consideration prior to application. However, this and other research demonstrate that it is inevitable that without any further management interventions high mobilization of P, dissolved organic matter and methane may persist for centuries following rewetting of peatlands. Abstract : Top soil removal prior to rewetting can be a suitable method to avoid the negative consequences of the excess release of phosphorus (P) and carbon post‐rewetting. We developed a simple decision support schematic to assist the peatland restoration process and to better understand the implications of top soil removal. Despite the potential benefits, top soil removal should not be declared as a universal method, as it requires detailed consideration prior to application. However, this and other research demonstrate that it is inevitable that without any further management interventions high mobilization of P, dissolved organic matter and methane may persist for centuries following rewetting of peatlands.